Leadership and self-deception getting out of the box by authors of arbinger institute - Baltabay, D.G. (KAZGUU Liberal Arts Digest Volume 3. M. NARIKBAYEV KAZGUU UNIVERSITY SCHOOL OF LIBERAL ARTS, 2022)
The book that is called «Leadership and self-deception. Getting out of the box» was published by a group of authors under the brand of the Arbinger Institute consulting company. The Arbinger Institute offers training, consulting, coaching and electronic tools to help people and organizations change their mindset, transform, stimulate innovation, resolve conflicts, and achieve sustainable improvement in results. The book offers an interesting and unexpected analysis of leadership problems in a modern organization. The book has told how the new leader of the fictional Zagrum Corporation abandoned his old ways of behaving and learned a new, more effective way of leadership. «Leadership and Self-Deception» has shown clear examples of what self-deception was, how it worked and, most importantly, how it can be overcome. The book has covered useful human skills, methods, and systems of leadership, this book goes deeper, fully covering the source of what makes leadership truly effective.
Keywords: elf-deception, blinders, get out of the box, leadership, self-betrayal